Dried blood spot technique for dietary fat assessment in a human nutritional intervention focused on oily fish intake - Laura Garcia-Urtiaga; Ainara Cano; Mercedes Caro; Jaione Pagaldai; Javier Amezaga; Itziar Tueros; Sara Arranz (Nutrition & Metabolism)
Abstract Background Several studies have employed dried blood spot (DBS) analysis to measure omega-3 levels in whole blood and investigate their associations with cardiovascular risk. Our study evaluated the effectiveness of using DBS as a marker for dietary intake, specifically focusing on omega-3 fatty acids, over both short- and long-term periods. As a novel approach, this study aims to determine whether the fatty acid (FA) profile of DBS can be useful to accurately reflect nutritional habits and monitor changes in fish intake over different consumption periods. Methods A within-subject nutritional intervention study was conducted with 18 healthy volunteers (both males and females aged 18–65 years). Their FA profiles were determined by GC-FID in DBS before the intervention began, and changes in their blood FA profiles were monitored at five different time-points across different periods of oily fish consumption. Dietary information was recorded daily through questionnaires. For statistical analysis, hierarchical clustering and principal component analysis were performed to detect patterns of FA profiles in DBS. Differences among groups were tested by Student´s t test or by Wilcoxon test, and changes across visits were analysed via linear mixed models. Results The results revealed three main patterns of the DBS profile, which could be explained by the participants’ dietary habits. Furthermore, the changes during the intervention indicated that eicosapentaenoic acid (20:5n-3) levels were highly affected by the diet of the previous day, whereas docosapentaenoic acid (22:5n-3) and docosahexaenoic acid (22:6n-3) required at least one or two weeks to show changes, with little difference depending on the FA levels of the participants before they started the intervention. Conclusion The use of DBS to examine blood FA composition is a promising, reliable and convenient way to assess dietary habits and monitor responses to food intake, which could help advance personalised nutritional strategies. Trial registration The study was registered at the ISRCTN (registration number ISRCTN47135203) the 22nd October 2024.